Deconstruction, Politics, Performatics - Burzynska, Anna R. (Modernity in Question, 2019)
In recent years, the terms "ethics," "politics," "performativity," and "experience" have proliferated throughout the discourse of the humanities. However, it is rarely noted that their contemporary understanding has been shaped by the works of Jacques Derrida, who has employed all these concepts since the mid-1960s. The aim of this book is to present the lesser discussed topics of Derrida's thought - not only as the creator of a specific mode of interpretation called "deconstruction" but also as an initiator of recent ethical and political reflection, a pioneer of performatics, and a precursor of current research on experience. At the same time, the book provides a panorama of the most important changes in the humanities of the last thirty years, and in particular - the ethical, performative, and empirical turns.